A high-performance computing framework for Monte Carlo ocean color simulations - Kajiyama, Tamito (2018)
The authors are grateful to Dr. Giuseppe Zibordi (E.C. Joint Research Centre, Italy) for his support from in situ marine radiometry perspectives. This study was supported by the Portuguese Foundation for Science and Technology (FCT/MEC) through the grant PEst-OE/EEI/UI0527/2011. Access to the Milipeia cluster (University of Coimbra, Portugal) was granted through the project 'Large-scale parallel Monte Carlo simulations for ocean colour applications.' Additional funding was granted through the ESA contract No. 22576/09/I-OL, ARG/003-025/1406/CIMA, and NOVA LINCS Ref. UID/CEC/04516/2013.